A global S. cerevisiae small ubiquitin‐related modifier (SUMO) system interactome. Issue 1 (28th May 2013) - Srikumar, Tharan; Lewicki, Megan C; Raught, Brian
<x xml:space="preserve">Abstract</x> The small ubiquitin‐related modifier (SUMO) system has been implicated in a number of biological functions, yet the individual components of the SUMO machinery involved in each of these activities were largely unknown. Here we report the first global SUMO system interactome. Using affinity purification coupled with mass spectrometry, we identify >450 protein–protein interactions surrounding the SUMO E2, Siz type E3s and SUMO‐specific proteases in budding yeast. Exploiting this information‐rich resource, we validate several Siz1‐ and Siz2‐specific substrates, identify a nucleoporin required for proper Ulp1 localization, and uncover important new roles for Ubc9 and Ulp2 in the maintenance of ribosomal DNA.